The Ability of PPKn Teachers In Implementing Higher Order Thinking Skills (HOTS) Based Learning At The 2 Gunungsitoli State High School - Trisman Zega; Fatiani Lase; Amstrong Harefa; Jesslyn Elisandra Harefa (Universitas Muhammadiyah Enrekang, 2023)
This research aims to find out how the ability of teachers in applying learning based on Higher Order Thinking Skills (Hots), the obstacles encountered by teachers and to know the efforts made by the teacher in overcoming obstacles in Applying Learning based on Hots in the State High School 2 Gunungsitoli. This research uses a descriptive approach with qualitative methods. The purpose of the use of a description approach is to find meaning that begins from the facts by performing observations recording all facts holistically scientifically with the observed problem. The research instrument used in this study was the researcher himself using his cell phones as a tool to record all the conversations, the results of images as real evidence, and a notebook that serves to record conversations with data sources or informants. The data collection techniques used are interviews, observations, and documentation. The results of the research and discussion concluded that: First, Teacher's Ability to Apply Higher Order Thinking Skills (Hots) in Higher High Schools (State Secondary Schools) is Ability in Preparing Learning Plans, Hots-driven Learning Design Ability, Asking Questions that Drive High Level Thinking, Supporting Students in Hots Thinking Processes, and Evaluating Hots Skills. Second, The obstacles faced by Teacher PPKn in Applying Higher Orders Thinking skills (HOTS) in high schools are The deep understanding of the concept of Hots learning material is still limited, The curriculum and evaluation are not supported, The time is limited because Hots Learning often requires longer time because it involves more in-depth thinking and complex, the availability of insufficient resources such as reading, learning materials, media or technology. Thirdly, the efforts made by Master PPKn in Applying Learning Based on Higher Order Thinking Skills (Hots) overcome the obstacles of providing training and development to teachers on Hots learning concepts and strategies, further providing learning resources and learning materials that support the application of Hots as well as monitoring and evaluation of implementation of learning Hots.